2021
DOI: 10.1007/s10439-021-02825-9
|View full text |Cite
|
Sign up to set email alerts
|

Automated Framework for the Inclusion of a His–Purkinje System in Cardiac Digital Twins of Ventricular Electrophysiology

Abstract: Personalized models of cardiac electrophysiology (EP) that match clinical observation with high fidelity, referred to as cardiac digital twins (CDTs), show promise as a tool for tailoring cardiac precision therapies. Building CDTs of cardiac EP relies on the ability of models to replicate the ventricular activation sequence under a broad range of conditions. Of pivotal importance is the His–Purkinje system (HPS) within the ventricles. Workflows for the generation and incorporation of HPS models are needed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Body surface potential maps and electro-anatomical maps, as well as cardiac sources, needed in various clinical applications, could be computed using reaction-Eikonal in pseudo-bidomain mode in approximately 35 min on a normal desktop machine with 8 cores. Validation of the underlying simulation in previous work reported in Gillette et al, 2021(Gillette et al, 2021a showed that ECGs acquired using the reaction-Eikonal method paired with lead fields gave comparable ECG morphologies to a traditional high-resolution, full bidomain simulation at a fraction of the costs. Such finedetailed full bidomain simulations on even a simpler biventricular setup without a physiologically-detailed His-Purkinje system lasting only 150 ms, required 30 min min on a HPC with 240 computing cores to compute both cardiac sources and potentials used to generate the same 12 lead ECG (Gillette et al, 2021a).…”
Section: Workflow Performancementioning
confidence: 73%
“…Body surface potential maps and electro-anatomical maps, as well as cardiac sources, needed in various clinical applications, could be computed using reaction-Eikonal in pseudo-bidomain mode in approximately 35 min on a normal desktop machine with 8 cores. Validation of the underlying simulation in previous work reported in Gillette et al, 2021(Gillette et al, 2021a showed that ECGs acquired using the reaction-Eikonal method paired with lead fields gave comparable ECG morphologies to a traditional high-resolution, full bidomain simulation at a fraction of the costs. Such finedetailed full bidomain simulations on even a simpler biventricular setup without a physiologically-detailed His-Purkinje system lasting only 150 ms, required 30 min min on a HPC with 240 computing cores to compute both cardiac sources and potentials used to generate the same 12 lead ECG (Gillette et al, 2021a).…”
Section: Workflow Performancementioning
confidence: 73%
“…Table 1 presents the patient cohort demographics, the LV, RV volume, and LV diameter derived from the mesh as described in ( Strocchi et al, 2020a ). A His-Purkinje network accounting for three LV fascicles (anterior and posterior, which further branches into two septal fascicles) and two RV fascicles (one septal fascicle and the moderator band) was generated for each mesh as described previously ( Gillette et al, 2021 ; Gillette et al, 2022 ). In the Supplement, we provide additional details about the construction of the His-Purkinje networks.…”
Section: Methodsmentioning
confidence: 99%
“…Developing a personalized digital twin of the heart, which integrates coherently and dynamically the patient’s clinical data over time, will likely be essential to overcome current challenges ( Corral-Acero et al, 2020 ; Lindemans, 2020 ; Gerach et al, 2021 ). Over the last decades, the digital twin heart has emerged as a modality to diagnose, understand and therapy complex arrhythmias ( Gillette et al, 2021a ; Gillette et al, 2021b ). This mini-review is structured as follows: Section 2 briefly summarizes the AF pathophysiology and current therapeutic modalities.…”
Section: Introductionmentioning
confidence: 99%